OREST – Công cụ xây dựng hệ chuyên gia dựa trên biểu diễn đối tượng và luật - Bao, Ho Tu; Khoi, Pham Ngoc; Lien, Doan Ngoc; Nga, Do Viet (Journal of Computer Science and Cybernetics, 2018)
We present in this paper some features of design and implementation of the OREST system. OREST is a general inference system, permitting building expert systems based on the representation of knowledge by objects and rules.